Study of familial Parkinson's disease in Russia, Uzbekistan, and Zambia. Issue 952 (8th February 2005) - Atadzhanov, M; Zumla, A; Mwaba, P
Abstract : Objective: The aims of this study were (A) to determine inheritance patterns of familial Parkinson's disease in three different geographical areas (Russia, Uzbekistan, and Zambia); (B) compare clinical characteristics of familial with sporadic Parkinson's disease; and (C) assess whether there were ethnic differences in clinical manifestations of the disease. Methods: Fifty two index cases of familial Parkinson's disease in Moscow, 55 in Tashkent, and 27 in Lusaka were selected on the basis of the typical clinical features of Parkinson's disease with a familial history. The sex ratio, transmission patterns, and segregation ratio were determined by pedigree analysis. Results: Familial Parkinson's disease was found in all three countries (30 families in Russia, 12 in Uzbekistan, and seven in Zambia), and appeared more common in Russia. Both autosomal dominant and autosomal recessive patterns of inheritance were seen, but autosomal dominance was more common in all countries. Conclusions: In all three countries men have a higher risk of developing Parkinson's disease than women and there are ethnic differences in clinical manifestations of the disease. The onset of both familial and sporadic Parkinson's disease in Zambian patients occurs at a younger age and is associated with slow progression and a benign course, and generally responds well to levodopa treatment.